Theileria in ruminants - Kiara, Henry K.; Steinaa, Lucilla; Nene, Vishvanath M.; Svitek, Nicholas (Springer, 2018)
Theileria are important hemoprotozoan parasites of domestic and wild ruminants, transmitted by ixodid ticks leading to diseases which range from mild in apparent reactions to highly fatal diseases. Bovine-infecting T. parva and T. annulata and ovine-infecting T. lestoquardi are of major global economic importance, but other Theileria spp. are also briefly mentioned. Classification of Theileria has been a subject of great controversy without consensus on whether many taxons are different species, synonyms, or subspecies of the same parasite. However, with the development of new molecular tools, many of the outstanding difficulties could be resolved. Theileria have complex life cycles both in the vertebrate host and the tick vector, many of which are not clearly understood. One unique feature of some Theileria is their ability to transform infected host cells into a reversible cancer-like proliferation conferring to them an ability to proliferate without apoptosis. The transformation is not permanent because it can be reversed by treatment with anti-theilerial drugs. Understanding this mechanism could give insights into treatment of cancer. Control of the diseases caused by Theileria has largely relied on chemical drugs either to treat infected hosts or prevent infection by controlling the tick vectors. But resistance to chemicals by the parasites or vectors has led to the development of more sustainable control methods such as live vaccination against the three most pathogenic Theileria spp. of ruminants. Efforts are also under way to develop subunit vaccines against these parasites.